Hallazgos imagenológicos en la enfermedad pleuropulmonar asociada al asbesto - Weisz C., José; Hasson A., Daniel; Palavecino B., Tamara (Revista Hospital Clínico Universidad de Chile, 2016)
Abestos-related pleuropulmonary disease involves a number of pathologic conditions that share inhalation exposure to asbestos fibers as a common factor. Dose and time of exposure have a role in the clinical manifestations of it, the main ones being benign pleural disease, asbestosis, malignant mesothelioma and bronchogenic carcinoma. Despite the ban on asbestos material usage in Chile, there is a long latency between exposure and clinical manifestations, which lead to it being still a relevant public health issue to this day. We present a series of representative images of abestos-related pleuropulmonary disease diagnosed at our centre. The pathogeny and radiologic manifestations are discussed, with an emphasis on the latter.